1983
DOI: 10.1007/bf00320275
|View full text |Cite
|
Sign up to set email alerts
|

An ABO-blood group abnormality leading to the detection of a colon-carcinoma

Abstract: A patient who had been admitted to hospital for surgical treatment of inguinal hernias was found to have group phenotype of A1B in the presence of a non-auto-anti-B. No previous records of the patient's blood group were available. The serological workup including absorption and saliva inhibition studies yielded a high probability for an acquired B-antigen which is known to be often associated with carcinoma of the colon. Subsequent coloscopy revealed the presence of a carcinoma of the sigmoid, unaccessable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Acquired B antigen has been thought to be asso ciated with neoplasms of the large bowel, and it has been suggested that following its detection a search should be made for such a lesion [Northoff et al, 1983]. Careful histological assessment of this patient's operative sample failed to reveal malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired B antigen has been thought to be asso ciated with neoplasms of the large bowel, and it has been suggested that following its detection a search should be made for such a lesion [Northoff et al, 1983]. Careful histological assessment of this patient's operative sample failed to reveal malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunological and biochemical analysis of whole mixed saliva is useful in the diagnosis of various systemic diseases such as Gougerot-Sjogren syndrome (Pennec et al 1982), colon carcinoma (Northoff et al 1983), and fucosidosis (Den Tandt & Jaeken 1979), as well as in studies of human genetics (Teng & Tan 1979, Herron et al 1980, Roberts et al 1981. One important component in these anaiyses are salivary enzymes.…”
Section: Introductionmentioning
confidence: 99%